Effect of peer counselors on exclusive breast feeding practices- A non randomized controlled trial in Belgaum district, Karnataka - P.R. Gunagi; V.A. Naik; M.D. Mallapur (Al Ameen Medical College, 2013)
Objectives: To study the effect of peer counselors on exclusive breast feeding practices. Methodology: The present non randomized controlled trial was conducted in PHC area; district Belgaum Karnataka during the period of November 2005 to Feb 2007. Amongst the two subcentres selected, one was taken as the study area and other as the control. Peer counselors selected from different localities of subcentre vantamuri (study area) underwent training on optimal breastfeeding practices, were recruited to give visits at regular intervals to mothers. All the mothers in the study and control group were visited independently by the investigator by making home visits once a month to know the breast feeding practices. Results: 60 women were enrolled in each group. The prevalence of Exclusive breastfeeding at 6 months was 40/60(66.67%) in the intervention group and 22/60(36.67%) in the control group (p=0.001). For the secondary outcomes, more number of mothers in the study group administered colostrum and initiated early breastfeeding. Conclusion: Peer counseling effectively increases early initiation, colostrum feeding, exclusive breastfeeding practices in the community